2013
DOI: 10.1039/c3nr33891f
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented inhibition of tubulin polymerization directed by gold nanoparticles inducing cell cycle arrest and apoptosis

Abstract: The effect of gold nanoparticles (AuNPs) on the polymerization of tubulin has not been examined till now. We report that interaction of weakly protected AuNPs with microtubules (MTs) could cause inhibition of polymerization and aggregation in the cell free system. We estimate that single citrate capped AuNPs could cause aggregation of ∼10(5) tubulin heterodimers. Investigation of the nature of inhibition of polymerization and aggregation by Raman and Fourier transform-infrared (FTIR) spectroscopies indicated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 70 publications
3
78
0
Order By: Relevance
“…Also, with AN treatment, both Bax and P53 expressions were upregulated, while both Bcl-2 and PARP-1 expressions were downregulated. 35 In our experiment with the treatment of the nanoemulsion containing AN (0.16 ppm) plus LP (0.4 µM), the expressions of procaspases 8, 3, and 9, as well as PARP-1 and Bcl-2 declined, while the Bax expression rose. Thus, it was postulated that the AN-LP nanoemulsion could accelerate apoptosis through the activation of caspases 8, 9, and 3, and through regulation by the mitochondria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, with AN treatment, both Bax and P53 expressions were upregulated, while both Bcl-2 and PARP-1 expressions were downregulated. 35 In our experiment with the treatment of the nanoemulsion containing AN (0.16 ppm) plus LP (0.4 µM), the expressions of procaspases 8, 3, and 9, as well as PARP-1 and Bcl-2 declined, while the Bax expression rose. Thus, it was postulated that the AN-LP nanoemulsion could accelerate apoptosis through the activation of caspases 8, 9, and 3, and through regulation by the mitochondria.…”
mentioning
confidence: 99%
“…34 In a similar study, Tsai et al 20 also reported that AN could activate caspase 3 to induce apoptosis after the treatment of leukemia cell, k562, with AN (5-6 nm) for 24 hours. More recently, Choudhury et al 35 further pointed out that AN could penetrate into lung cancer cell, A549, for conjugation with micro-organelle to induce apoptosis with arrest at G0/G1. Also, with AN treatment, both Bax and P53 expressions were upregulated, while both Bcl-2 and PARP-1 expressions were downregulated.…”
mentioning
confidence: 99%
“…Such a color transition is often indicative of changes in the metal oxidation state (Fujiwara et al 2007). The increase in the background may be due to the aggregation happened in the synthesized non-purified AuNPs-C. tora leaf conjugates (Choudhury et al 2013). It is well known that the particles aggregate the background scattering.…”
Section: Plasmon Resonancementioning
confidence: 99%
“…Plenty of evidence has shown that NPs can induce cell cycle arrest at different phases of the cell cycle. Some studies have indicated that gold NPs treatments could induce significantly increased cell-doubling times and more cell cycle arrest at the sub-G0/G1 phase [18] or S phase [29] than the control treatments, indicating that not all cells could complete the whole cell cycle after being exposed to gold NPs. Cell cycle analyses have suggested that Fe 3 O 4 NPs [32] and SiO 2 NPs [24] both resulted in G2/M arrest in PC12 cells, as well as an increase in the rate of apoptosis.…”
Section: Cellular Physiological Activity Changesmentioning
confidence: 99%
“…Inorganic NPs can range in size from 1-100 nm and have a high surface area-to-volume ratio; thus, they have marked reactivity and particle-to-cell contact and can be internalized by nerve cells, subsequently affecting the cytoskeleton system [18,19], which is important for sustaining fundamental cellular morphology. The cytoskeleton is composed of MTs, microfilaments (MFs), and intermediate filaments (IFs).…”
Section: The Effects Of Inorganic Nps On the Cytoskeletonmentioning
confidence: 99%